Kinetic Models for Healing of the Subduction Interface Based on Observations of Ancient Accretionary Complexes. (16th July 2019) - Fisher, D. M.; Smye, A. J.; Marone, C.; van Keken, P. E.; Yamaguchi, A.
Abstract: Sand‐shale mélanges from the Kodiak accretionary complex and Shimanto belt of Japan record deformation during underthrusting along a paleosubduction interface in the range 150 to 350 °C. We use observations from these mélanges to construct a simple kinetic model that estimates the maximum time required to seal a single fracture as a measure of the rate of fault zone healing. Crack sealing involves diffusive redistribution of Si from mudstones with scaly fabric to undersaturated fluid‐filled cracks in sandstone blocks. Two driving forces are considered for the chemical potential gradient that drives crack sealing: (1) a transient drop in fluid pressure ∆P f, and (2) a difference in mean stress between scaly slip surfaces in mudstones and cracks in stronger sandstone blocks. Sealing times are more sensitive to mean stress than ∆P f, with up to four orders of magnitude faster sealing. Sealing durations are dependent on crack spacing, silica diffusion kinetics, and magnitude of the strength contrast between block and matrix, each of which is loosely constrained for conditions relevant to the seismogenic zone. We apply the model to three active subduction zones and find that sealing rates are fastest along Cascadia and several orders of magnitude slower for a given depth along Nicaragua and Tohoku slab‐top geotherms. The model provides (1) a framework for geochemical processes that influence subduction mechanics via crack sealing and shear fabric development and (2) demonstration that kinetically driven mass redistribution during the interseismic period is a plausible mechanism for creating asperities along smooth, sediment‐dominated convergent margins. Plain Language Summary: Geophysical monitoring of active subduction zones has revealed plate boundary slip behaviors such as creep, slow slip events, and earthquakes that vary spatially and temporally for different plate boundaries and downdip along a given boundary. Fault rocks exposed on land from paleosubduction plate boundaries provide a record of the deformation processes that likely occur during slip along active boundaries, so we review the characteristics of these ancient rocks to develop insight into slip behavior in subduction zones. We find that plate boundary deformation in these cases occurs within a wide fault zone through processes that involve redistribution of silica from shearing mudstones to cracking sandstone blocks. We use a geochemical model to calculate how long it would take to seal a crack by this process and conclude that cracks seal at rates that could influence the earthquake cycle, with rates of crack healing dependent on the temperature structure and the depth where slip occurs. Our results suggest that processes of frictional failure and geochemical healing in downgoing sediments may influence the slip stability along the subduction interface. Key Points: Microstructural observations of subduction mélange record dissolution along a scaly fabric and diffusion to cracks in sandstone blocks A silica kinetics model depicts crack healing that is highly dependent on temperature and slab‐top geotherm Kinetic healing of cracks could modulate fault zone strength during the interseismic period